Diversidade e estrutura genética de Euterpe edulis Mart - Carvalho, Marina Santos (2015)
Euterpe edulis Mart., popularly known as juçara palm tree is an endemic palm tree of the Atlantic Forest that has been passing through an intense process of extractivism due to palm tree exploration, a product of high alimentary value. Due to the forest fragmentation and the extractivism, the juçara palm tree may be losing its genetic diversity and becoming more inclined to enter in extinction. The objective of this work was to evaluate the diversity and genetic structure in six municipalities of the South region of the state of Espírito Santo, aiming to generate information that may be used in programs of conservation and breeding of the species. Materials from 20 populations were collected, six of these populations with 39 individuals belonging to the South sub-region and 14 populations with 121 individuals from the Caparaó subregion, totalizing 160 individuals. Thirteen microsatellite primers were used. The SSR amplified a total of 86 alleles which varied from five to 11 alleles per loci, with an average of 6.62 alleles. The polymorphism information content was higher than 0.56 in all the loci. The expected heterozygosity was higher than the observed in all the populations and the fixation index was positive indicating excess of homozygotes. The diversity indexes showed moderate differentiation among the 20 evaluated populations (FST=0.18; GST=0.17; RST=0.23) and endogamy presence (FIS = 0,35). The values of these parameters were similar among the populations of each subregion, nevertheless Caparaó presented higher endogamy (FIS=0,37) and the South region presented higher differentiation (FST=0.19). The analysis of molecular variance indicated elevated variation among the populations (80.64%) with moderated value of FST (0.18). On the cluster produced by the UPGMA method, three groups were formed, and on the evaluation done by the program STRUCTURE best K, equal to 3 was obtained. All the groups were formed by populations of more than one locality and mainly of the same geographic origin. Considering the existence of populations compounded by divergent individuals and others that present high level of homozygosity it is necessary to use materials of diverse sources aiming to preserve and maintain the diversity. The information of this work reinforce the necessity of X implementing and delineating public politics as support and development of breeding programs of the species aiming to determine management methods and species conservation